Glufosinato de amonio para el control de malezas en el cultivo de banano (Musa AAA) en el Ecuador - Galarza Reinoso, Sandy Isabel (2024)
Banana cultivation is one of the largest economic items for Ecuador, due to the fact that it is the main exporter worldwide, so that this crop is not exempt from the attack of agricultural pests, including the attack of weeds that can cause a decrease in world banana production of approximately 14 %. Among the tools in weed control in banana cultivation are herbicides, which are chemical products that affect the normal functioning of plants. They are effective to apply but if not used properly they could cause damage to the crop.Glufosinate-ammonium has limited transport within the plant and its action is basically contact. Its mechanism of action is inhibition of the enzyme glutamine synthetase in nitrogen metabolism. Blocking this enzyme builds up ammonia in plants, which destroys cell membranes.It is recommended to spray with good soil moisture and adequate coverage of the weed foliage. Do not use on soils prone to alkalinity. Because it could cause irreparable damage to the soil. These herbicides are widely used in banana crops because they are responsible for combating almost all the weeds present in the crop.